2021
DOI: 10.3847/1538-4357/ac0c82
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Jets in Double-peaked Emission-line AGN in the KISSR Sample

Abstract: Double-peaked emission-line AGN (DPAGN) have been regarded as binary black hole candidates. We present here results from parsec-scale radio observations with the Very Long Baseline Array (VLBA) of five DPAGN belonging to the KISSR sample of emission-line galaxies. This work concludes our pilot study of nine type 2 Seyfert and LINER DPAGN from the KISSR sample. In the nine sources, dual compact cores are only detected in the “offset AGN,” KISSR 102. However, the overall incidence of jets in the eight sources th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 87 publications
1
18
0
Order By: Relevance
“…Based on 6 GHz VLA observations of SDSS quasi-stellar objects, Kellermann et al (2016) have ★ E-mail: vaishnavrao@iitb.ac.in suggested RQAGN to be those having 21 ≤ log[L 6 (W Hz −1 )] ≤ 23. Radio observations have revealed that most Seyferts possess subparsec or parsec-scale radio emission (e.g, de Bruyn & Wilson 1976;Ulvestad & Wilson 1984;Roy et al 1994;Thean et al 2001;Kharb et al 2021) and 40% display kpc-scale radio structures (KSRs; Gallimore et al 2006;Singh et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Based on 6 GHz VLA observations of SDSS quasi-stellar objects, Kellermann et al (2016) have ★ E-mail: vaishnavrao@iitb.ac.in suggested RQAGN to be those having 21 ≤ log[L 6 (W Hz −1 )] ≤ 23. Radio observations have revealed that most Seyferts possess subparsec or parsec-scale radio emission (e.g, de Bruyn & Wilson 1976;Ulvestad & Wilson 1984;Roy et al 1994;Thean et al 2001;Kharb et al 2021) and 40% display kpc-scale radio structures (KSRs; Gallimore et al 2006;Singh et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…3). Such double-peaks have been attributed to several different sources, such as the presence of dual AGN (Rubinur et al 2019;Maschmann et al 2020), AGN-driven outflows (Nevin et al 2018;Rakshit & Woo 2018;Kharb et al 2021) or rotating discs (Eracleous et al 2009). In our analysis, we find such double-peaks in the non-rotating spherical system, which are caused solely due to the presence of lateral outflows caused by the jet (see Fig.…”
Section: Nature Of Jet-ism Interactions and Their Spatial Extentmentioning
confidence: 49%
“…We now turn our attention to much smaller spatial scales than probed by the GMRT and VLA observations. We focus on the KPNO Internal Spectroscopic Survey Red (KISSR; [115]) sample of Seyfert and LINER galaxies [116]. This sample was chosen based on the presence of doublepeaked emission lines in their SDSS spectra as well as a radio detection in the VLA FIRST survey [117].…”
Section: Signatures Of Jet + Wind Feedback On Parsec-scalesmentioning
confidence: 99%